Hypoxia modulates the phenotype of mechanically stressed endothelial cells responding to CoCr-enriched medium - Machado, Mariana Issler Pinheiro [UNESP]; Gomes, Anderson Moreira [UNESP]; Zambuzzi, Willian Fernando [UNESP] (Elsevier, 2024)
Given the importance of the endothelial cell phenotype in dental peri-implant healing processes, the aim of this study was to better assess the involvement of endothelial cells responding to cobalt-chromium (CoCr)-enriched medium. Biologically, cobalt is widely used molecule to induce chemical experimental hypoxia because it stabilizes hypoxia inducible factors (HIF1α). The aplication of hypoxia models provides better experimental condition to allow its impact on cellular metabolism, by looking for biochemical and molecular issues. Thus, this study looks for understaing whether CoCr-based materials are able to modulate endothelial cells considering the hypoxic effect prmoted by cobalt. Firstly, our data shows there is a siginificant effect on endothelial phenotype by modulating the expression of VEGF and eNOS genes, whith low requirement of genes related with proteasome intracellular complex. Importantly, the data were validated using classical chemical modulators of hypoxia signaling [chrysin (5,7-dihydroxyflavone) and Dimethyloxalylglycine (DMOG)] in functional assays. Altogether, these data validate the hypothesis that hipoxya is important to maintain the phenotype of endothelial cells, and it is properly interesting during the tissue regeneration surrounding implants and so compromising osseointegration process. Finally, it is important to mention that the cobalt released from CoCr devices might contribute with an sufficient microenvironment surrounding implanted devices and it paviments new roads looking for more bioactive surfaces of implantable materials in human health.
Keywords: Biomaterials; Blood vessel; Chromium; Cobalt; Endothelial cell; Hypoxia; Implants